Manejo de bionator en tratamientos ortopédicos en relación a la maloclusión infantil - Jimbo Villalta, Angie Carolina (2024)
The management of pediatric malocclusion presents a significant challenge in pediatric dentistry. This study examines the use of the bionator, a functional orthopedic appliance, in the treatment of Class I, II, and III malocclusions in children. The main objective isto evaluate the effectiveness of the bionator in correcting these conditions and preventing long-term orthodontic complications. This research project adopts a documentary methodology that focuses on the collection and analysis of relevant bibliographic sources. Therefore, comprehensive searches are conducted in databases such as PubMed, Scielo, Elsevier, and Medigraphic, using key terms such as "Bionator," "pediatric malocclusion," and "orthopedic treatments." In addition, articles and books published in the last ten years are selected according to specific inclusion criteria to ensure both the relevance and timeliness of the data collected. The study is conducted in three phases: (1) searching for and collecting information, (2) organizing the data into a content matrix, and (3) analyzing and systematizing the results. The results indicate that the bionator is generally effective in correcting moderate malocclusions and improves alignment across all classes of malocclusion. However, its effectiveness varies regarding the stimulation of mandibular growth and the regulation of the eruption of permanent teeth. In conclusion, although the bionator offers several advantages, its effectiveness may vary depending on specific design factors of the appliance and the individual characteristics of each patient. These findings emphasize the importance of careful treatment selection and continuous monitoring throughout the orthodontic process